2017
DOI: 10.1371/journal.pone.0190445
|View full text |Cite
|
Sign up to set email alerts
|

Lung microRNA deregulation associated with impaired alveolarization in rats after intrauterine growth restriction

Abstract: Intrauterine growth restriction (IUGR) was recently described as an independent risk factor of bronchopulmonary dysplasia, the main respiratory sequelae of preterm birth. We previously showed impaired alveolarization in rat pups born with IUGR induced by a low-protein diet (LPD) during gestation. We conducted a genome-wide analysis of gene expression and found the involvement of several pathways such as cell adhesion. Here, we describe our unbiased microRNA (miRNA) profiling by microarray assay and validation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Interestingly, ET-1 CpG methylation was also significantly reduced in F1 IUGR rat sperm, suggesting epigenetic modifications as a potential mechanism for the multigenerational transmission of these IUGR phenotypes, via the paternal line ( 56 ). In line with this finding, altered expression of various miRNAs were found in lung tissues at day 10, day 21, and 5 months after birth of IUGR rat offspring whose mothers were either undernourished ( 68 ) or fed with a low-protein diet ( 67 ) during pregnancy. Most of these miRNAs ( miR-29, miR-128-3p, miR-34c-5p, miR-19b-3p, miR-449a-5p , and miR-30e-5p ) are involved in lung development and injury-repair ( 67 , 68 ).…”
Section: Intrauterine Growth Restriction and The Associated Altered E...supporting
confidence: 63%
See 1 more Smart Citation
“…Interestingly, ET-1 CpG methylation was also significantly reduced in F1 IUGR rat sperm, suggesting epigenetic modifications as a potential mechanism for the multigenerational transmission of these IUGR phenotypes, via the paternal line ( 56 ). In line with this finding, altered expression of various miRNAs were found in lung tissues at day 10, day 21, and 5 months after birth of IUGR rat offspring whose mothers were either undernourished ( 68 ) or fed with a low-protein diet ( 67 ) during pregnancy. Most of these miRNAs ( miR-29, miR-128-3p, miR-34c-5p, miR-19b-3p, miR-449a-5p , and miR-30e-5p ) are involved in lung development and injury-repair ( 67 , 68 ).…”
Section: Intrauterine Growth Restriction and The Associated Altered E...supporting
confidence: 63%
“…In line with this finding, altered expression of various miRNAs were found in lung tissues at day 10, day 21, and 5 months after birth of IUGR rat offspring whose mothers were either undernourished ( 68 ) or fed with a low-protein diet ( 67 ) during pregnancy. Most of these miRNAs ( miR-29, miR-128-3p, miR-34c-5p, miR-19b-3p, miR-449a-5p , and miR-30e-5p ) are involved in lung development and injury-repair ( 67 , 68 ). Microarray analysis and homologous analysis of brain tissues containing hippocampus from growth restricted F1 rats whose mothers received a 50% reduction in food intake throughout pregnancy also revealed 49 rat genes that are homologous in humans, and had a negative correlation between gene expression and DNA methylation status ( 60 ).…”
Section: Intrauterine Growth Restriction and The Associated Altered E...supporting
confidence: 63%
“…Investigating AFSC-EV mechanism of action, we found that their beneficial effects on fetal lung tissue were exerted, at least in part, via miRNAs that regulate the expression of genes involved in lung development (5). Particularly, AFSC-EVs were highly enriched in members of the miR17~92 cluster, which is known to control lung branching morphogenesis (9), lung progenitor cell proliferation and differentiation (10,11), surfactant protein C secretion (12), and alveolarization (11). However, the mechanisms underlying the lung regenerative effects of AFSC-EV administration remain to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Non-coding RNA continue to be studied in the context of alveolarization, and while changes in the lung steady-state levels of mRNA, lncRNA, circRNA, and microRNA (miR) have been reported in hyperoxia-based BPD models in mice (615), the bulk of these recent studies have addressed miRs (21,419). Descriptive reports continue to emerge that associate altered steady-state levels of multiple miR species with stunted alveolarization, including IUGR (136). Temporal changes in miR-431 steady-state levels were noted during rat lung development (560), which is interesting given another in vitro study implicating miR-431-5p in surfactant expression (311).…”
Section: Non-coding Rnamentioning
confidence: 89%